Big five personality construct and consumer buying behaviour in Singapore. - Lim, Ivan Jit Boon. (2008)
To further explore the utility and robustness of the ‘Big Five’ personality construct, this study extends the research to Singapore and finds evidence of the same personality structure there. This study is further extended to find a correlation between the Big Five personality construct and common patterns of consumer buying behaviour, and takes a closer look at the impact of the Big Five personality construct on respondents segmented by gender, race and age.